ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN: (Studi Kasus Pada PT. Kereta Api Property Manajemen Tulungagung) - Ade Cahyo Wicaksono; Nurani; Annisa Sulihandini (Universitas Tulungagung, 2022)
Quality encourages customers to establish a strong relationship with the company, while satisfaction is a fulfillment response from consumers which is determined by the customer's perception of product or service performance. This research aims to determine the effect of service quality variables on customer satisfaction both simultaneously and partially as well as the independent variables that have a dominant effect on the dependent variable. As research objects are variables X1 tangible, X2 responsiveness, X3 assurance, X4 empathy and X5 reliability and customer satisfaction. As a result, simultaneously there is a positive and significant influence of service quality variables on customer satisfaction, meaning that the better the service quality, the higher the customer. The t test shows that partially the tangible, responsiveness, assurance, empathy and reliability variables have a significant effect on customer satisfaction at PT. Tulungagung Property Management Railway.